The global financial crisis and the shift to shadow banking - Yeva Nersisyan; L. Randall Wray (Intervention. European Journal of Economics and Economic Policies, 2010)
While most economists agree that the world is facing the worst economic crisis since the Great Depression, there is little agreement as to what caused it. Some have argued that the financial instability we are witnessing is due to irrational exuberance of market participants, fraud, greed, too much regulation, etc. However, some post-Keynesian economists following Minsky have argued that this is a systemic problem, a result of internal market processes that allowed fragility to build over time. In this paper we focus on the shift to the 'shadow banking system' and the creation of what Minsky called the Money Manager phase of capitalism. In this system, rapid growth of leverage and financial layering allows the financial sector to claim an ever rising proportion of national income – what is sometimes called 'financialization' – as the financial system evolved from hedge to speculative and finally to a Ponzi scheme. The policy response to the financial crisis in the US and elsewhere has largely been an attempt to rescue money manager capitalism. Moreover, in the case of the US the bailout policy has contributed to further concentration of the financial sector, increasing dangers. We believe that the policies directed at saving the system are doomed to fail – and that alternative policies should be adopted. The effective solution should come in the way of downsizing the fi - nancial sector by two-thirds or more, and effecting fundamental modifications.
Keywords: 330